PENGARUH PEMBERIAN FERMENTASI LERI (AIR CUCIAN BERAS) PADA PERTUMBUHAN BIBIT PADI (Oriza sativa, L) VARIETAS INPARI 42 - Syafi'i, Ach; Kristiana, Lia; Awidiyantini, Ruly (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2025)
Rice washing water contains glutelin protein and vitamin B1 which can be used as organic fertilizer. Fermentation is the process of decomposing complex compounds in rice washing water into simple compounds that can be used as fertilizer for plants. This study aims to determine the effect of the application of Leri fermentation (Rice Washing Water) on the growth of rice seedlings (Oryza Sativa L.) inpari 42 variety. This study was conducted for 25 days from June 16 to July 10, 2024 in Nyalabu Daya Village, Pamekasan District, Pamekasan Regency. This study was arranged based on a Complete Randomized Design (CRD) with 5 treatments and 4 replications consisting of P1 (Control), P2 (25 ml), P3 (50 ml), P4 (75 ml), P5 (100 ml). In this study, the parameters observed included plant height, root length, leaf length, leaf width, and wet weight. Data were analyzed using Analysis of Variance (ANOVA) at the 5% level to determine the differences between treatments and parameters observed using the least significant difference test (LSD). The results showed that the provision of fermented rice washing water had an effect on increasing the growth of leaf length and leaf width but had no effect on the growth of plant height, root length, and wet weight.